Fixed-dose ivermectin for Mass Drug Administration: Is it time to leave the dose pole behind? Insights from an Individual Participant Data Meta-Analysis - Echazu, Adriana; Bonanno, Daniela; Fleitas, Pedro Emanuel; Jacobson, Julie; Matamoros, Gabriela; Mwandawiro, Charles; Enbiale, Wendemagegn; de Jesus, Áuria; Brooks, Alan; Krolewiecki, Alejandro Javier (PLOS Neglected Tropical Diseases, 2025)
Background Ivermectin (IVM) is widely used in mass drug administration (MDA) programs for the control of neglected tropical diseases (NTDs). Current regimens rely on weight- or height-based dosing, which lead to operative challenges. This study evaluates an age-based fixed-dose regimen for IVM. Methodology This is an individual participant data (IPD) meta-analysis including anthropometric data from over 700,000 individuals, across 53 NTD-endemic countries. Fixed-dose regimens were developed based on weight distribution by age. The proportion of individuals achieving the target range dose (200–400 µg/kg) was assessed and compared to traditional dosing regimens. Principal Findings Fixed-doses of 3 mg for pre-school children (PSAC), 9 mg for school-aged children (SAC), and 18 mg for women of reproductive age (WRA) resulted in a higher proportion of participants receiving the target dose compared to weight- and height-based regimens (79.9% vs. 32.7% and 37.3%, respectively, p < 0.001). Underdosed individuals were fewer with fixed-dose (8.7%) compared to weight-based (32.6%) and height-based (46.3%) regimens. Although doses above the target range increased slightly, most remained within 600 µg/kg. Conclusions An age-based fixed-dose regimen for IVM could improve treatment coverage and simplify MDA activities. Simplified logistics could lead to cost savings in drug distribution and administration, improving the overall efficiency of MDA programs. These findings support the inclusion of currently excluded PSAC in IVM-based MDA interventions. More broadly, this paper provides evidence for considering the potential policy and programmatic implications of fixed-dose IVM. This Individual Participant Data Meta-analysis (IPD-MA) is registered in PROSPERO (CRD42024521610).